An Analysis on Spurt of Cancer Cases in Amaravati River Basin, Tamil Nadu, India – Evidence Based Research - S, Sujitha; R, Sindhu; D, Prabu; M, Rajmohan; Dhamodhar, Dinesh (International Journal of Scientific Research in Biological Sciences, 2025)
Background: Environmental health tracking is an emerging area that spans the traditional public health and environmental protection sectors. Aim: To investigate whether carcinogens in the Amaravti river belt are associated with increased cancer cases in Karur and Tirupur districts, Tamil Nadu. Materials and Method: Carcinogens were identified based on the "International Agency for Research on Cancer" lists of carcinogens with cancer sites. Between 2011 and 2022, cross-sectional studies were included in the study. The levels of cadmium, hexavalent chromium, nickel, lead, arsenic, nitrite/nitrate, and phosphates in drinking water were compared with the WHO standard limits. The number of cancer cases recorded in each district was determined using data from the Tamil Nadu Cancer Registry Project for 2021. Results: The study found the levels of nickel and arsenic in the Amaravati River Basin to be in the range of 0-0.090 and 0.358-0.961, respectively. Nickel levels are fourfold higher than the WHO standard limits for drinking water, while arsenic levels are fifty-fold higher. Conclusion: There is evidence that shows the presence of carcinogens in the vegetable samples collected in the Karur district, indicating contamination has already entered the human food chain.